2011
DOI: 10.4100/jhse.2011.62.04
|View full text |Cite
|
Sign up to set email alerts
|

Triathlon: swimming for winning

Abstract: Olbrecht J. Triathlon: swimming for winning. J. Hum. Sport Exerc. Vol. 6, No. 2, pp. 233-246, 2011. Swimming performance in triathlon gradually gets of overriding importance in view of the final positioning in a race. It is important to end up swimming in the leading group(s) and to consider the impact of the swim stage on the 2 remaining sports disciplines in order to outbalance the athlete's effort and to be able to keep racing for a good position until the end of the race. Unlike cycling and running where t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 39 publications
3
32
0
Order By: Relevance
“…As it was observed that the aerobic metabolism did not directly influence the TLim-vVO 2 max, it was hypothesized that the anaerobic performance capacity could be a very relevant parameter to this specific type of exercise, as suggested before (Fernandes et al, 2003b). However, TLim-vVO 2 max did not present any relationship with [La − ]max and Δ[La − ] in the TLim-vVO 2 max test; probably, the oxidation of lactate during performance may account for this unexpected result, mainly in expert swimmers, in which the lactate removal ability was found to be higher (Olbrecht, 2000). …”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…As it was observed that the aerobic metabolism did not directly influence the TLim-vVO 2 max, it was hypothesized that the anaerobic performance capacity could be a very relevant parameter to this specific type of exercise, as suggested before (Fernandes et al, 2003b). However, TLim-vVO 2 max did not present any relationship with [La − ]max and Δ[La − ] in the TLim-vVO 2 max test; probably, the oxidation of lactate during performance may account for this unexpected result, mainly in expert swimmers, in which the lactate removal ability was found to be higher (Olbrecht, 2000). …”
Section: Introductionmentioning
confidence: 87%
“…Once swimming may be considered as an aerobic sport, in which the anaerobic system contribution has significant influence (Capelli et al, 1998; Gastin, 2001; Figueiredo et al, 2011), maximal oxygen consumption (VO 2 max) plays a central role among the energy-yielding mechanisms (di Prampero, 1986); in fact, several authors consider this parameter as the expression of maximal metabolic aerobic performance capability of a subject and, therefore, related to one of the primary areas of interest in swimming training and performance diagnostic (Olbrecht, 2000; Libicz et al, 2005; Rushton, 2007; Sousa et al, 2011). However, and despite the fundamental areas of interest in swimming are already identified (Smith et al, 2002; Rushton, 2007), the study of the maximum duration of exercise in which the intensity corresponding to the minimum velocity that elicits VO 2 max (vVO 2 max) can be maintained is scarcely studied.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations